2017
DOI: 10.1016/j.jaci.2016.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of fractional exhaled nitric oxide measurement in predicting cough-variant asthma and eosinophilic bronchitis in adults with chronic cough: A systematic review and meta-analysis

Abstract: The present meta-analyses indicated the diagnostic potential of Feno measurement as a rule-in test for detecting CVA in adult patients with chronic cough. However, Feno measurement may not be useful to predict EB in nonasthmatic subjects with chronic cough. These findings warrant further studies to validate the roles of Feno measurement in clinical practice of patients with chronic cough.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 35 publications
1
69
1
Order By: Relevance
“…Exhaled nitric oxide can be used as a surrogate marker of eosinophilic airway inflammation and steroid responsiveness in classic asthma, but its role in asthma and chronic cough is questioned (see later). A meta-analysis of observational studies showed exhaled nitric oxide to have a relatively high specificity of 0.85 in predicting asthma among adult patients with chronic cough [46]; however, there is still no consensus on the cut-off level for the diagnosis. Blood eosinophilia is a simple and readily available measure, but is characterised by diurnal and seasonal variability [47], so multiple assessments should be made [48].…”
Section: Phenotypes Of Chronic Coughmentioning
confidence: 99%
“…Exhaled nitric oxide can be used as a surrogate marker of eosinophilic airway inflammation and steroid responsiveness in classic asthma, but its role in asthma and chronic cough is questioned (see later). A meta-analysis of observational studies showed exhaled nitric oxide to have a relatively high specificity of 0.85 in predicting asthma among adult patients with chronic cough [46]; however, there is still no consensus on the cut-off level for the diagnosis. Blood eosinophilia is a simple and readily available measure, but is characterised by diurnal and seasonal variability [47], so multiple assessments should be made [48].…”
Section: Phenotypes Of Chronic Coughmentioning
confidence: 99%
“…Type 2 airway inflammation contributes to cough hypersensitivity at peripheral levels and is frequent in asthma. Thus, the detection of type 2 airway inflammation using objective tools, such as induced sputum analyses or fractional exhaled nitric oxide tests,85 may help relieve asthma-related cough in chronic cough patients 86. However, cough in asthma appears to have more complex nature than expected, particularly among asthmatic patients already receiving asthma-specific treatment.…”
Section: Clinical Implication Of Cough Hypersensitivity In Various Comentioning
confidence: 99%
“…Cough due to asthma can be classifi ed as cough-variant asthma, in which cough is the sole symptom; cough-predominant asthma, which can include dyspnea and wheezing; and cough that persists despite therapy with corticosteroids and beta agonists. 4,5 Of note, while variable airfl ow obstruction is classically detected in asthmatic patients, some patients exhibit no abnormal spirometry results. 6,7 Therefore, additional pulmonary tests are often needed, such as methacholine challenge and fraction of exhaled nitric oxide (FeNO) measurement.…”
Section: Diagnostic Testsmentioning
confidence: 99%